Model Penguatan Kemandirian Ekonomi Pesantren Melalui Pengembangan Potensi Produk Halal di Pesantren An-Nasyiin Pamekasan - Wahyu Setiawan Djodi; Taufiqur Rahman (Al Maal: Journal of Islamic Economics and Banking, 2023)
Research conducted as an effort to advance the economy of pesantren through the development of a model of economic independence for pesantren needs to be carried out to create Islamic boarding schools that are superior and competitive in creating quality graduates.  The research conducted at the An-Nasyiin Pamekasan Islamic boarding school became the main focus in developing the economic independence of the pesantren through strengthening the potential of halal products.  This research was conducted using qualitative methods using a descriptive analysis approach, as well as using various techniques of analysis, collection, and validity of data to support more optimal research results.  Therefore, the research conducted by researchers aims to provide a significant solution in the form of providing a model for strengthening the economic independence of pesantren, so that pesantren throughout Indonesia have a view on how to strengthen the economic independence of pesantren so that they are not too dependent on other parties, especially for Islamic boarding schools an-Nasyi'in Pamekasan.  This research produces a practical answer in the form of a flow model of economic independence that can be applied to build Islamic boarding school economic independence that involves various parties in the implementation proces.